An examination of consumers' adoption of internet of things (IoT) in Indian banks - Fatehi Almugari; Parul Bajaj; Mosab I. Tabash; Adil Khan; Mohammed Ashraf Ali (Cogent Business & Management, 2020)
The purpose of this study is to find out the impact of awareness, privacy & safety, cost, convenience, social influence, and habits on the adoption of IoT in Indian banks. The sample size of 467 Indian customers has been taken for the study. The Confirmatory Factor Analysis (CFA) is applied for testing the reliability and validity as well as the suitability of the questionnaire for the research. Moreover, the Structural Equation Modeling (SEM) model is used for testing the hypotheses of the study, both CFA model fit and SEM model indices are found satisfactory in comparison with recommended values. The results reveal that convenience, social influence, privacy & safety, and awareness have a significant impact on the adoption of the internet of things in Indian banks. On the other hand, the results show that cost & habits do not have an influencing impact on the adoption of IoT. The current study is an attempt to examine the adoption of the internet of things in Indian banks. In India, there is a huge scope of application of IoT in different sectors as India is aiming at being a developed country and no doubt, such kind of technology in the banking services can be a basis for it. The current paper is an attempt to help the policymakers as well as the producers of IoT objects to create that kind of service in the banks that can be easily adoptable and beneficial to the public.
Keywords: 650; IoT; internet of things; banks; banking sector; cost; convenience; awareness; social influence; privacy; safety; adoption